COMPARISON OF COPPER LEVELS IN NORMAL PREGNANCY WOMEN AND SEVERE PREECLAMPSIA - Tia Reza; Ariadi Ariadi; Yusrawati Yusrawati (STIKES Syedza Saintika Padang, 2022)
Hypertension in pregnancy is one of the obstetric complications that cause a lot of morbidity and mortality in the field obstetrics, in addition to bleeding and infection. The incidence of severe preeclampsia is only 5-10% of all pregnancies but is a major cause of maternal and fetal death and is a major contributor to preterm labor. It is currently estimated that severe preeclampsia accounts for 50,000 deaths annually worldwide, in addition to the presence of this disease will increase the need for intensive neonatal care. The purpose of this research is to determine the difference in copper concentration in normal pregnant women with pregnant women with severe preeclampsia. This research is a diagnostic research with approach used is cross sectional study in maternity hospital room of Obstetrics and Gynecology Department of Faculty of Medicine Universitas Baiturrahmah since September 2016-March 2017. Obtained sample of 60 people who meet inclusion and exclusion criteria. The calculation is done by taking blood samples of patients and examined the level of copper. Data analysis was done univariant and bivariate by using T dependent test. there were significant differences in copper levels in patients with severe preeclampsia and normal pregnancy, where the p value <0.05, and the mean test with 95% confidence level was between 0.767-1.023 at 0.895. This means there is a significant difference in copper levels in severe preeclampsia and normal pregnancy. There were significant differences in copper levels in patients with severe preeclampsia and normal pregnancy.Keywords: Copper, Preeclampsia.